Ist eine gute Schule eine inklusive Schule? Entwicklung von Messinstrumenten durch Schulinspektionen - Piezunka, Anne (Verlag Julius Klinkhardt, 2020)
Due to the UN Convention on the Rights of Persons with disabilities, the Federal States of Germany have to implement inclusive education. However, there is no shared understanding how to define inclusive education in Germany. Therefore, different understandings on how to implement inclusive education within the schools exist. Comparing different Federal States of Germany, Anne Piezunka examines how school inspectorates define inclusive education. School inspectorates are part of the educational administration. They evaluate the quality of schools and are a key means of accountability. Evaluating the quality of schools, they analyze documents, conduct interviews and observe classes. Thereby, they apply several metrics. For example: "The class starts on time". Every federal state has developed its own metrics. Piezunka analyzes which metrics school inspectorates apply to evaluate the implementation of inclusive education on the school level. Interviewing the developers of metrics, she also studies the development of these metrics and seeks to explain differences between the federal states. The study brings together sensemaking theory, sociology of evaluation and research on inclusive education. (DIPF/Orig.)